Evaluating the Laplace pressure of water nanodroplets from simulations. (14th March 2018) - Malek, Shahrazad M A; Sciortino, Francesco; Poole, Peter H; Saika-Voivod, Ivan
Abstract: We calculate the components of the microscopic pressure tensor as a function of radial distance r from the centre of a spherical water droplet, modelled using the TIP4P/2005 potential. To do so, we modify a coarse-graining method for calculating the microscopic pressure (Ikeshoji et al 2003 Mol. Simul .29 101) in order to apply it to a rigid molecular model of water. As test cases, we study nanodroplets ranging in size from 776 to 2880 molecules at 220 K. Beneath a surface region comprising approximately two molecular layers, the pressure tensor becomes approximately isotropic and constant with r . We find that the dependence of the pressure on droplet radius is that expected from the Young–Laplace equation, despite the small size of the droplets.